Management practices of primary dysmenorrhea among female high school students in Nekemte town, East Wallaga Zone, Western Oromia, Ethiopia: a cross-sectional study - Bekan Gudata Gindaba; Lemane Dereje Sebu; Ebisa Zerihun Gindaba; Misgana Tesgara Abdisa; Damiso Geneti Dinagde; Chala Regassa Hunde; Kidane Dinku Motuma; Takele Mitiku Tesema; Tesfaye Abera Gudeta (BMC Women's Health)
Abstract Background Primary dysmenorrhea is a common gynecological condition characterized by recurring, cramp-like abdominal pain before or during menstruation in the absence of pelvic disease. Despite its high prevalence, management practices remain unstudied, particularly among adolescent students. This study examined pharmacological and nonpharmacological management strategies for primary dysmenorrhea among female high school students in Nekemte town, Ethiopia. Objectives To assess the management practices for primary dysmenorrhea among high school students in Nekemte town, East Wallaga, Western Oromia, Ethiopia. Methods This institutional-based cross-sectional study was conducted from November 6 to December 6, 2024, among 422 female high school students who experienced primary dysmenorrhea. The participants were selected via a multistage stratified sampling technique. The data were collected via a structured questionnaire and analyzed via SPSS version 25. A paired t-test was used to assess differences in pain scores before and after the interventions, whereas multiple linear regression was used to evaluate the effectiveness of nonpharmacological methods. Results Among the participants, 80.1% utilized nonpharmacological management, including drinking tea (20.2%), drinking ginger tea (15.8%), and sleeping (16.7%). Diclofenac (53.1%) was the most commonly used pharmacological treatment. Tukey post hoc analysis revealed that ibuprofen (n = 13, M = 3.54, SD = 2.22) significantly reduced pain scores more than diclofenac did (n = 26, M = 1.65, SD = 1.70). A paired t-test revealed a significant reduction in pain scores after both pharmacological (p < 0.001) and nonpharmacological (p < 0.001) interventions. Multiple linear regression indicated that sports (p = 0.040) and hot baths (p = 0.026) significantly reduced pain scores. Conclusion Many students rely on self-medication for their management of primary dysmenorrhea. Moreover, both pharmacological and nonpharmacological interventions were associated with reducing pain, with sports and hot baths showing significant benefits. Greater awareness and education on safe and effective pain management strategies are recommended. Schools and healthcare providers should collaborate to promote evidence-based dysmenorrhea management practices.